Double loop reconstruction following pancreaticoduodenectomy for malignant tumor: Short-term outcome. (2016) - Limongelli, Paolo; D'Alessandro, A.; Parisi, S.; Pirozzi, R.; Bondanese, M.; Colella, C.; Docimo, Giovanni; Del Genio, Gianmattia; Del Genio, Alberto; Docimo, Ludovico
Abstract: Background: To evaluate the use of a double loop reconstruction following pylorus preserving proximal pancreaticoduodenectomy (PPPPD). Methods: Morbidity and mortality were evaluated in 55 patients undergoing PPPPD for malignant tumors, followed by a double loop reconstruction. Results: The mean intra-operative blood loss was 908 mL ± 531. In-hospital mortality was 5.4% (3/55 pts). The mean length of hospital stay was 17 ± 5 days (range 12–45 days). Postoperative complications occurred in 25 patients (46.2%). Five patients developed an anastomotic leak, one biliary and four pancreatic (4/55; 7%). Delayed gastric emptying occurred in 8 patients (14.5%). Reoperation was required in two patients for hemorrhage. Conclusions: A double loop alimentary reconstruction following PPPPD led to a low incidence of DGE and pancreatic fistula. Although mortality rate was higher than that reported by referral centres, this technique has been performed in a not specialized unit attaining acceptable results.